2018
DOI: 10.24843/itepa.2018.v07.i01.p01
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH pH EKSTRAKSI TERHADAP RENDEMEN, SIFAT FISIKO-KIMIA DAN FUNGSIONAL KONSENTRAT PROTEIN KACANG GUDE (Cajanus cajan (L.) Millsp.)

Abstract: The purpose of this research are to know the effect of pH extraction on yield, physico-chemical and functional properties of pigeon pea protein concentrate, and also to know the appropriate pH extraction to obtain the best yield and properties of pigeon pea protein concentrate. The research was using Randomized Complete Design with pH extraction treatment which consist of five levels were 9; 9,5; 10; 10,5; and 11. The parameters were observed consist of yield, physical properties (lightnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
3
0
5
Order By: Relevance
“…The heating process for a long time can cause a change in protein structure. The results of the research by Pratiwi, Yusasrini, & Putra (2018), the yield produced in the manufacture of protein concentrate from gude beans ranged from 12.87% to 17.29%, while the yield of cowpea protein concentrate produced using 70% ethanol was 4.85 % (Adhibuana, Hintono and Pramono, 2018) and the yield of red bean protein concentrate is 13.69% (Piñuel et al, 2019).…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating process for a long time can cause a change in protein structure. The results of the research by Pratiwi, Yusasrini, & Putra (2018), the yield produced in the manufacture of protein concentrate from gude beans ranged from 12.87% to 17.29%, while the yield of cowpea protein concentrate produced using 70% ethanol was 4.85 % (Adhibuana, Hintono and Pramono, 2018) and the yield of red bean protein concentrate is 13.69% (Piñuel et al, 2019).…”
Section: Yieldmentioning
confidence: 99%
“…The high yield was influenced by the protein solubility of black bean protein concentrate. The research results by Pratiwi, Yusasrini, & Putra, (2018) showed that the higher the protein solubility, the higher the yield of the product. Factors that influence protein solubility include molecular weight, amino acid composition, pH, type of solvent, processing condition, and temperature.…”
Section: Yieldmentioning
confidence: 99%
“…Meningkatnya pH dipengaruhi oleh banyaknya gugus amin yang menangkap proton (atom H) yang berasal dari kitosan. Pratiwi et al, (2018), menyatakan bahwa interaksi gugus amin dan atom H yang berlebih dapat meningkatkan pH protein menjadi 8-10. Hal ini juga menunjukkan bahwa adsorpsi kitosan-protein tidak hanya dapat meningkatkan kadar protein tetapi juga dapat meningkatkan pH limbah cair tahu.…”
Section: Adsorpsi Protein Limbah Cair Tahu Dengan Kitosanunclassified
“…Proses denaturasi protein ini memicu terjadinya pembentukan agregasi dan gelasi atau pembentukan gel. Hal ini dikarenakan bahwa ketika terjadi denaturasi, maka semua protein dalam suspensi menyatu dan membentuk struktur matriks protein (Pratiwi, Yusasrini, & Putra, 2018). Hasil ini selaras dengan laporan dari Tay, Xu, & Perera (2005) yang menyatakan bahwa gelasi protein terjadi ketika protein beragregasi membentuk jaringan atau matriks.…”
Section: Tingkat Kekerasan (Hardness)unclassified
“…Nilai kohesivitas berbanding lurus dengan kadar protein dan nilai kekerasan. Hal ini terkait dengan kadar protein yang semakin tinggi, dengan suhu penggumpalan yang tinggi yaitu 83 °C maka akan terjadi denaturasi protein, proses agregasi dan pembentukan gel sehingga terjadi gelasi protein yang akan meningkatkan kekerasan dan kohesivitas produk tahu (Pratiwi et al, 2018).…”
Section: Kohesivitasunclassified